IMPLEMENTASI METODE CUSTOMER SATISFACTION INDEKS DALAM ANALISIS KEPUASAN PASIEN TERHADAP PELAYANAN KLINIK SALSABILA - Alfiarini, Alfiarini; Apriadi, Deni (Jurnal Teknik Informasi dan Komputer (Tekinkom), 2024)
To support government programs in improving the quality of human resources through quality health services. Good service quality can be seen from the following factors, the first is physical evidence where customers will see direct evidence of the service provided, the second is reliability, namely the extent to which the company has a level of reliability in providing services, the third is responsiveness, where the service is provided. provided quickly, precisely and the information conveyed is clear, the third is guarantee, namely the service provided can provide trust and confidence, the fifth is empathy, where the company tries to understand what customers want. Currently, the Salsabila Clinic still has difficulty measuring the level of satisfaction with the services provided to patients, so the level of satisfaction cannot be measured whether the services provided are in line with expectations or not. To measure the level of service quality, there are many methods that can be used, one of which is the Customer Satisfaction Index (CSI) method. The results of measurement calculations using the CSI method can be used to determine the level of patient satisfaction with staff service, cleanliness and facilities at the Salsabila clinic. The results of this research are the patient satisfaction index for Salsabila Clinic services of 78% with a Satisfaction Likert scale